Reflectance and fast polarization dynamics of a GaN/Si nanowire ensemble. (10th July 2018) - Korona, K P; Zytkiewicz, Z R; Sobanska, M; Sosada, F E; Dróżdż, P A; Klosek, K; Tchutchulashvili, G
Abstract: Optical phenomena in an ensemble of high-quality GaN nanowires (NWs) grown on a Si substrate have been studied by reflectance and time-resolved luminescence. Such NWs form a structure that acts as a virtual layer that specifically reflects and polarizes light and can be characterized by an effective refractive index. In fact we have found that the NW ensembles of high NW density (high filling fraction) behave rather like a layer of effective medium described by the Maxwell Garnett approximation. Moreover, light extinction and strong depolarization are observed that we assign to scattering and interference of light inside the NW ensemble. The wavelength range of high extinction and depolarization correlates well with transverse localization wavelength estimated for such an ensemble of NWs, so we suppose that these effects are due to Anderson localization of light. We also report results of time-resolved measurements of polarization of individual emission centers including free and bound excitons (D 0 XA, 3.47 eV), inversion domain boundaries (IDB, 3.45 eV) and stacking faults (SF, 3.42 eV). The emission of the D 0 XA and SF lines is polarized perpendicular to GaN c -axis while the 3.45 eV line is polarized along the c -axis which supports a hypothesis that this line is emitted from IDBs. Time-dependent depolarization of luminescence is observed during the first 0.1 ns after excitation and is interpreted as the result of interaction of the emission centers with hot particles existing for a short time after excitation.